2018
DOI: 10.1080/13880209.2018.1492620
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on phytochemistry, pharmacology, and flavonoid biosynthesis ofScutellaria baicalensis

Abstract: Context:Scutellaria baicalensis Georgi (Lamiaceae) is a popular medicinal plant. Its roots are used as the famous traditional Chinese medicine Huang-Qin, which is recorded in Chinese Pharmacopoeia, European Pharmacopoeia, and British Pharmacopoeia.Objective: This review comprehensively summarizes research progress in phytochemistry, pharmacology, and flavonoid biosynthesis of S. baicalensis.Methods: English and Chinese literature from 1973 to March 2018 was collected from databases including Web of Science, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
191
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(194 citation statements)
references
References 154 publications
1
191
0
2
Order By: Relevance
“…These include inhibition of PGE2 synthesis and G 0 , G 1 , G 2 , and S phase arrest. Scutellaria also has neuroprotective and hepatoprotective affects (Wang et al, 2018b). In TCM, it is said to clear heat from the body and is typically used to eliminate toxins.…”
Section: Qingre (Formulas and Herbs That Clear Heat)mentioning
confidence: 99%
“…These include inhibition of PGE2 synthesis and G 0 , G 1 , G 2 , and S phase arrest. Scutellaria also has neuroprotective and hepatoprotective affects (Wang et al, 2018b). In TCM, it is said to clear heat from the body and is typically used to eliminate toxins.…”
Section: Qingre (Formulas and Herbs That Clear Heat)mentioning
confidence: 99%
“…is considered as another key factor that affects the contents of medicinal active ingredients. Previous studies have shown that the contents of medicinal active ingredients in S. baicalensis after harvesting are closely related to enzyme activities in roots ( Wang et al, 2018b ; Zhao et al, 2016b ). The active ingredients such as baicalin and wogonoside in fresh roots are easily reduced in enzyme solution under humid environment or washing and soaking in water ( Liu, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… Name Molecular formula Weight Plant part Ref. 1 Baicalein (5,6,7-Trihydroxyflavone) C 15 H 10 O 5 270 Root Hairy Root [ 37 ] 2 Methoxybaicalein (5,6-Dihydroxy-7-methoxyflavone) C 16 H 12 O 5 284 Root [ 117 ] 3 Scutellarein (5,6,7,4′-Tetrahydroxyflavone) C 15 H 10 O 6 286 Root [ 39 ] 4 5,6,7-Trihydroxy-4′-methoxyflavone C 16 H 12 O 6 300 Aerial part [ 38 ] 5 Oroxylin A (5,7-Dihydroxy-6-methoxyflavone) C 16 H 12 O 5 284 Root [ 37 ] 6 Tenaxin II (5,7,2′-Trihydroxy-6-methoxyflavone) C 16 H 12 O 6 300 Root [ 38 ] 7 5,7,4′-Trihydroxy-6-methoxyflavone C 16 H 12 O 6 300 Aerial part [ 38 ] 8 …”
Section: Phytochemistrymentioning
confidence: 99%